A Note on Determining Which of J Parameters Has the Largest or Smallest Value - Wilcox, Rand (Advances in Social Sciences Research Journal, 2022)
This note suggests two simple approaches to determining whether it is reasonable to make a decision about which random variable has the smallest or largest measure of location. Both are related to Tukey’s three-decision rule, they are easily adapted to a wide range of situations, and they have certain advantages over extant techniques. The focus is on trimmed means, but the method is easily adapted to a wide range of situations. One version of the proposed approach is based on a variation of the percentile bootstrap that has not been previously studied.